Money and Information (Nóema, 2016)
Money and information are both signs of human civilization. Their connection with language is evident. Their value is based on confidence regarding the creativity of human work. Today menace is to reduce money and information to pure goods.
Keywords: Money; Information; Sign; Language; Value; Goods; Confidence